A Systematic Review of Economic and Government Policy Issues in the Production of Biofuels by Microalgae - Onoriasakpobare, Felix Omamuyovwe; Ukolobi, Odiri; Chukuka, Vivian Ishioma; Onianwah, Ifeanyichukwu Fidelis; Adeola, Morenike Omotayo (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Research has shown that the initial supply and environmental benefits of conventional biofuels may have been exaggerated, even if they have strong legal support. Due to negative externalities related to the distribution of resources and food, the long-term viability of switching to biofuels is being called into question more and more. This study highlights the need for additional research into a third-generation feedstock based on algae while examining the advantages and disadvantages of traditional biofuels. Given the many benefits of this technology, the study offers recommendations on how a regulatory framework may support microalgae as a source of biofuels.